GenMOnto : A strategic domain ontology modelling approach for conceptualisation and evaluation of collective knowledge for mapping genomes. Issue 2 (17th February 2020) - Shreyas, K.; Deepak, Gerard; Santhanavijayan, A.
Abstract: Knowledge representation and query generation have been important areas of interest for researchers. The rising demand for data to be characterised in a manner that is comprehensible by both humans and computers has turned their attention to ontologies. Genome mapping is a domain which currently has no ontologies, and hence the need was felt to create an ontology in this domain. The domain has been studied comprehensively, and important concepts and semantic relationships have been recognised. Protégé has been used to visualise the ontology, and it has also been depicted in OWL format. An overall reuse ratio of 0.8 was achieved for the proposed ontology.